Pengaruh Insentif, Fasilitas Kerja Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada Perumdam Tirta Daroy Kota Banda Aceh - Indah Mirissa; Lukman T. Ibrahim; Isthafan Najmi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Human resource management is an activity that must be carried out by every company to produce quality human resources. Perumdam Tirta Daroy Banda Aceh City implements an incentive program as additional income outside of salary or wages for Perumdam Tirta Daroy Banda Aceh City to encourage increased employee work productivity. The aim of this research is to determine the magnitude of the influence of incentives, work facilities and motivation on employee work productivity at Perumdam Tirta Daroy, Banda Aceh City. The employee population at Perumdam Tirta Daroy, Banda Aceh City is 215 employees and the sample taken after using the Slovin formula is 68 employees. Based on the results of the t test (partial) the incentive variable value tcount>ttable (2.489>1.669), with a significant value of 0.000 <0.05. This means that incentives have a partial effect on employee work productivity, then the test results (partial) regarding the work facility variable have a value of tcount>ttable (1.767>1.669), with a significant value of 0.000 <0.05. This means that work facilities have a partial effect on employee work productivity and the results of the t test (partial) work motivation variable value tcount>ttable (1.772>1.669), with a significant value of 0.000 <0.05. This means that work motivation has a partial effect on employee work productivity. Based on the results of the f test (simultaneous), it was concluded that the value of Fcount>Ftable was (8.889>2.750), with a significant value of 0.000 <0.05. This means that incentives, work facilities and work motivation simultaneously influence employee work productivity at Perumdam Tirta Daroy, Banda Aceh City